Impact Assessment of Training Programmes: a case study of MANAGE - Vikram Singh; G. Jaya; A.S. Charyulu (Journal of Agricultural Extension Management, 2025)
The National Institute of Agricultural Extension Management, (MANAGE) is an apex organization under the aegis of Ministry of Agriculture, Government of India. Training being the major mandate of MANAGE, aims to bring change in knowledge, attitude, behaviour and skills of the trainees so that job performance in the organization is improved for superior results